Dive Behaviour of Belugas (Delphinapterus leucas) in the Shallow Waters of Western Hudson Bay - Martin, A.R.; Hall, P.; Richard, P.R. (ARCTIC, 2001)
Beluga diving was studied in western Hudson Bay, where the preferred habitat of this whale in summer is shallow coastal waters. No relationship was found between the duration of a dive and the surface interval either preceding or following it. During rare periods of intense diving, 77% of an average dive cycle was spent below the water surface. Only in waters deeper than 25 m did any whale spend more than half its time below the surface zone; in rivers, less than 15% of the time was spent at depths of 4 m or more. The frequency of long dives increased with water depth. Maximum dive duration was 15.6 min. Dives to depths of 25 m or less were of variable duration and time-depth profile; most dives exceeding 50 m had a square profile and reached the seabed. The easterly migration in early September took the whales into water deeper than 100 m for the first time in several months, and they dived frequently to the bottom during this period. No clear difference in dive capability was found between western Hudson Bay belugas and those that inhabit deeper waters farther north. The preference of this population for shallow water in summer is not dictated by an inability to dive to greater depths; belugas can utilize benthic resources throughout Hudson Bay. On a étudié le bélouga en plongée dans l'ouest de la baie d'Hudson, où les eaux littorales peu profondes constituent l'habitat estival préféré de cette baleine. On n'a trouvé aucun lien entre la durée de la plongée et l'intervalle passé en surface qui la précède ou la suit. Durant les rares périodes de plongée intense, 77 p. cent d'un cycle moyen de plongée se déroulait sous la surface de l'eau. C'est seulement dans les eaux dont la profondeur était supérieure à 25 m que les baleines passaient plus de la moitié du temps sous la zone en surface; dans les cours d'eau, moins de 15 p. cent du temps se passait à des profondeurs de 4 m ou plus. La fréquence des longues plongées augmentait avec la profondeur de l'eau. La durée maximale de la plongée était de 15,6 mn. Les ...